Sistem Informasi Geografis Lokasi Lahan Kelapa Sawit Berbasis Android Di Kecamatan Mootilango - hariati Husain (Jurnal Informatika Upgris, 2019)
The development of information technology that exists today, making the utilization of information technology energy developing. Mootilango Sub-District is one of the districts that have enough land to make the area of palm oil land is about 182.170 (Ha) for the location of oil palm land owned by 90 people. Monitoring of plantation land is still less rapid, consequently it still takes a long time to obtain information about the state of the palm oil itself. During this time the data and location information of plantations presented are still in the form of reports containing numbers and texts. This method used is Research and Development method, this application is designed using PHP programming language software and HTML, Macromedia Dreamwever, Java programming language using Android Studio, and tools for modeling using Unified Modeling Language (UML). The conclusion of this research is the geographic information system can be applied and petrified the monitoring of plantation land more effectively and efficiently.